If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + 4b) + (c + -2d) = 0 Remove parenthesis around (a + 4b) a + 4b + (c + -2d) = 0 Remove parenthesis around (c + -2d) a + 4b + c + -2d = 0 Solving a + 4b + c + -2d = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4b' to each side of the equation. a + 4b + c + -4b + -2d = 0 + -4b Reorder the terms: a + 4b + -4b + c + -2d = 0 + -4b Combine like terms: 4b + -4b = 0 a + 0 + c + -2d = 0 + -4b a + c + -2d = 0 + -4b Remove the zero: a + c + -2d = -4b Add '-1c' to each side of the equation. a + c + -1c + -2d = -4b + -1c Combine like terms: c + -1c = 0 a + 0 + -2d = -4b + -1c a + -2d = -4b + -1c Add '2d' to each side of the equation. a + -2d + 2d = -4b + -1c + 2d Combine like terms: -2d + 2d = 0 a + 0 = -4b + -1c + 2d a = -4b + -1c + 2d Simplifying a = -4b + -1c + 2d
| 12=22-2x | | 8=3k-3 | | 25+N-100=75 | | 11/20x-1/4x | | 10 x 1/L x 57.8 | | 15.5y+12=12 | | 9x+26=3x+20 | | 4x-3x^3=0 | | 3y+y=72 | | 5x-3x=3+4x | | y=8-x^2-2x | | 8/3:x=4/5:3 | | x+75=2x-20 | | (4+1)*3= | | (2+4)*1= | | 9-3*1= | | N+7n-2=22 | | 2a+2b=86 | | 3-8/4= | | Log(x)+2-2x=0 | | 6/2*3 | | 5+7*6= | | 30r^2-30r=0 | | 6/2x4 | | Ln(x)+2-2x=0 | | x^3-10*x^2+19*x+30=0 | | x^4-10*x^3+19*x^2+30*x=0 | | 2x-4(14x-6)=0 | | (x-6)2=188 | | 2x-12-2x-12-y-y=360 | | y^3-8y^3/2=64 | | 4y-(6*(-3)+6y*(-3))=26 |